Otkir Hoshimov's " Lifes passed in a dream" (Journal of Science-Innovative Research in Uzbekistan, 2023)
Otkir Hoshimov is one of the great uzbek writers whose works are still the favourite ones for every booklover. His works are like water for the soul. While reading Hoshimov's novels a reader imagines oneself as the main character. His works open a new world for every reader. Regardless of the topic of his novel and story, he awakens a deep feeling in the soul of every reader